2018
DOI: 10.1007/s11064-018-2529-4
|View full text |Cite
|
Sign up to set email alerts
|

MiR-183-5p Alleviates Chronic Constriction Injury-Induced Neuropathic Pain Through Inhibition of TREK-1

Abstract: MicroRNAs have been implicated in nerve injury and neuropathic pain. In the previous study we had shown that miR-96 can attenuate neuropathic pain through inhibition of Nav1.3. In this study, we investigated the role of miR-183, a same cluster member of microRNA with miR-96, in neuropathic pain and its potential mechanisms. We found that the expression level of miR-183-5p in dorsal root ganglion was decreased with the development of neuropathic pain induced by chronic constriction sciatic nerve injury (CCI). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…Our study showed that the levels of microRNA-122 were downregulated in the DRGs of CCI rats on the 1st day after nerve injury but were upregulated by early GCSF treatment. Many studies have investigated the temporal profiles of microRNA expression in the DRGs of CCI rats, but those studies usually focused on microRNA expression in the late stage after nerve injury and did not achieve consistent results [18][19][20][21]24,25]. Li et al [19] screened the expression of different microRNAs in the DRGs of CCI rats by microarray analysis with quantitative reverse transcriptase PCR and found that the levels of microRNA-341 are upregulated on the 14th day after nerve injury.…”
Section: Gcsf Upregulated Microrna-122 Expression In the Drgs Of CCI mentioning
confidence: 99%
See 3 more Smart Citations
“…Our study showed that the levels of microRNA-122 were downregulated in the DRGs of CCI rats on the 1st day after nerve injury but were upregulated by early GCSF treatment. Many studies have investigated the temporal profiles of microRNA expression in the DRGs of CCI rats, but those studies usually focused on microRNA expression in the late stage after nerve injury and did not achieve consistent results [18][19][20][21]24,25]. Li et al [19] screened the expression of different microRNAs in the DRGs of CCI rats by microarray analysis with quantitative reverse transcriptase PCR and found that the levels of microRNA-341 are upregulated on the 14th day after nerve injury.…”
Section: Gcsf Upregulated Microrna-122 Expression In the Drgs Of CCI mentioning
confidence: 99%
“…However, alterations in the microRNA expression were not evaluated at an early time point in their study. Other studies focused on different microRNAs and showed that the levels of microRNA-21 [20] and microRNA-146a-5p [18] are upregulated but that the levels of microRNA-96 [21], microRNA-183-5p [24], and microRNA-34a [25] are downregulated in the DRGs of CCI rats in the late stage after nerve injury (>3 days). Zhang et al [22] and Sun et al [23] showed that the levels of microRNA-141 and microRNA-206 in the DRGs of CCI rats decrease from the 1st day after nerve injury and are more significantly decreased on the 7th day after nerve injury.…”
Section: Gcsf Upregulated Microrna-122 Expression In the Drgs Of CCI mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, transducer channels, such as TRPA1, can occur as a consequence of miR-449a down-regulation [113]. The only potential change counteracting these proalgesic alterations refers to the down-regulated miR-183-5p that targets potassium channel Trek1, a two pore domain potassium channel subfamily member 2 (Kcnk2), which as a leak current keeps the membrane potential hyperpolarized [106]. The up-regulation of this channel may counteract the brake set on potassium channel expression by the miR-17-92 cluster.…”
Section: Mirnas Deregulated In the Peripheral Nervementioning
confidence: 99%